STR markers based genetic diversity evaluation of Chilika buffalo of Odisha state - RS Kataria; Ravinder Singh; S Lavakumar; Ankita Gurao; SK Mishra; SK Niranjan; V Vohra; SK Dash (Journal of Livestock Biodiversity, 2025)
The study was conducted to genetically characterize the Chilika buffalo breed of Odisha state using microsatellite (STR) markers allelic diversity. Blood samples of 48 unrelated animals were collected randomly from different regions of breeding tract and DNA was extracted from whole blood using standard protocol. Genetic diversity was assessed using 23 heterologous bovine microsatellite markers previously reported, through PCR ampli ication and fragment analysis on an automated DNA sequencer. A suf icient allelic diversity was observed with a mean of 3.97 alleles per locus. The mean observed heterozygosity in the population was 0.593, suggesting animals under random mating. Additionally, three quantitative tests were employed namely the sign test, standardized difference test, and Wilcoxon sign rank test along with a qualitative test for mode shift distortion of allelic frequencies, which showed that the population has not undergone any genetic bottleneck in the recent past. The results indicate Chilika buffalo though a small population has been maintaining suf icient genetic diversity